The impact of anti-inflammatory drugs on facial odontogenic cellulitis in children: a cross-sectional study in France - Lucille Poure; Caroline Delfosse; Thomas Trentesaux; Fleur Maury; François Dubos; Romain Nicot; Thomas Marquillier (BDJ Open)
Abstract Objective Dental caries is defined by the WHO as a multifactorial non-communicable disease. If left untreated, it can progress to abscesses and then head and neck odontogenic cellulitis. It requires immediate, appropriate, and interdisciplinary treatment. The aim of this study was to draw up an epidemiological profile of these children treated at the Lille University Hospital in northern France and to study the impact of self-medication of anti-inflammatory drugs. Materials and Methods A single-centre retrospective, cross-sectional study was conducted on children with odontogenic cellulitis admitted to the paediatric emergency department of the Lille University Hospital between March 2013 and December 2021. Results 15.3% of the 636 children included had taken nonsteroidal anti-inflammatory drugs before going to the emergency department. The frequency of pain and trismus was higher in children who had taken nonsteroidal anti-inflammatory drugs than in those who had not. Frequency of hospitalisation was higher in children who had not taken nonsteroidal anti-inflammatory drugs than for those who had (70% vs. 57%, respectively; p < 0.05). Inversely, the mean length of stay was longer for children who had taken nonsteroidal anti-inflammatory drugs than in those who had not (1.1 vs. 0.8 days, respectively; p < 0.05). Conclusion This first French epidemiological study on odontogenic cellulitis in children underlines the need to develop multidisciplinary prevention and patient education.